2009
DOI: 10.1073/pnas.0809650106
|View full text |Cite
|
Sign up to set email alerts
|

Female rats learn trace memories better than male rats and consequently retain a greater proportion of new neurons in their hippocampi

Abstract: Learning increases the survival of new cells that are generated in the hippocampal formation before the training experience, especially if the animal learns to associate stimuli across time [Gould E, Beylin A, Tanapat P, Reeves A, Shors TJ (1999) Nat Neurosci 2:260 -265]. All relevant studies have been conducted on male rats, despite evidence for sex differences in this type of learning. In the present study, we asked whether sex differences in learning influence the survival of neurons generated in the adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 62 publications
5
92
2
2
Order By: Relevance
“…Tasks that require a functional hippocampus such as trace eyeblink conditioning showed improved learning during the proestrus [25][26][27], while studies using spatial learning tasks, reported impairments in learning during the proestrus phase on the radial arm maze [28] or during the estrus phase in the Morris water maze [29,30]. We detected no effect of the estrous cycle phase on the learning of the CHB in mice.…”
Section: Discussionmentioning
confidence: 42%
“…Tasks that require a functional hippocampus such as trace eyeblink conditioning showed improved learning during the proestrus [25][26][27], while studies using spatial learning tasks, reported impairments in learning during the proestrus phase on the radial arm maze [28] or during the estrus phase in the Morris water maze [29,30]. We detected no effect of the estrous cycle phase on the learning of the CHB in mice.…”
Section: Discussionmentioning
confidence: 42%
“…The results have functional implications because of the known effects of estrogens and VEGF in hippocampus, such as stimulation of postnatal neurogenesis in the dentate gyrus (16,18,43). The results of the present study suggest that the effects of estrogens on neurogenesis may be mediated, at least in part, by their ability to increase VEGF in the neurogenic niche.…”
Section: Figmentioning
confidence: 57%
“…It was found that associative learning increases the survival of new neurons in the adult hippocampus, regardless of temporal contiguity (Leuner et al 2006). Cell survival was later shown to be regulated by the acquisition and not memory expression (Anderson et al 2011), the sex of the animals (Dalla et al 2009), and the degree of task difficulty. Indeed, establishing a contextual conditioned stimulus representation acquired in a single training trial is not sufficient to change the survival of cells born 10 d before exposure to the task (Pham et al 2005).…”
Section: Effect On Cell Numbersmentioning
confidence: 99%